HUBUNGAN PENGETAHUAN IBU HAMIL DENGAN KEPATUHAN KONSUMSI TABLET BESI (FE) DIPUSKESMAS RAWAT INAP SIDOMULYO - Septia, Qori Armiza; Yulita, Emi; Halimah, Siti; Hayati, Iznirrahma; Saputri, Tiara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Anemia is a condition where the number of red blood cells or the amount of hemoglobin (oxygen-carrying protein) is below normal. Iron supplementation or administration of Fe tablets is an important effort in preventing and treating anemia, especially iron deficiency anemia. Compliance in consuming iron tablets is the obedience of pregnant women in carrying out the recommendations of health workers to consume iron tablets. The purpose of this study was to determine the relationship between knowledge of pregnant women and adherence to consumption of iron (Fe) tablets at the Sidomulyo Inpatient Health Center. The benefit of this research is to increase knowledge information, especially in the scope of midwifery research so that it can add insight and knowledge about Iron (Fe) Tablet Consumption Compliance. This type of research, using cross sectional method. The place for taking cases at the Sidomulyo Inpatient Health Center starts from August 2 to. The sampling technique used by accidental sampling method is part of the population, namely 43 pregnant women. Processing and analysis of data using chi square. The results of this study indicate: there is a relationship between maternal adherence in consuming fe tablets and adherence to consumption of iron (fe) tablets at the Sidomulyo inpatient health center. The chi-square statistical test shows that the knowledge variable can be seen with a P value of 0.000 (P <0.05. It is suggested to provide and improve information about the benefits of Fe tablets so that people are motivated to obey iron tablets.Keywords: Knowledge, Compliance, and Fe Tablets.